Modulation of gaba release from the thalamic reticular nucleus by cocaine and caffeine: role of serotonin receptors - Goitia, Belén (2015)
Serotonin receptors are targets of drug therapies for a variety of neuropsychiatric and neurodegenerative disorders. Cocaine inhibits the re-uptake of serotonin (5-HT), dopamine, and noradrenaline, whereas caffeine blocks adenosine receptors and opens ryanodine receptors in the endoplasmic reticulum. We studied how 5-HT and adenosine affected spontaneous GABAergic transmission from thalamic reticular nucleus. We combined whole-cell patch clamp recordings of miniature inhibitory post-synaptic currents (mIPSCs) in ventrobasal thalamic neurons during local (puff) application of 5-HT in wild type (WT) or knockout mice lacking 5-HT2A receptors (5-HT2A−/−). Inhibition of mIPSCs frequency by low (10 μM) and high (100 μM) 5-HT concentrations was observed in ventrobasal neurons from 5-HT2A−/− mice. In WT mice, only 100 μM 5-HT significantly reduced mIPSCs frequency. In 5-HT2A−/− mice, NAN-190, a specific 5-HT1A antagonist, prevented the 100 μM 5-HT inhibition while blocking H-currents that prolonged inhibition during post-puff periods. The inhibitory effects of 100 μM 5-HT were enhanced in cocaine binge-treated 5-HT2A−/− mice. Caffeine binge treatment did not affect 5-HT-mediated inhibition. Our findings suggest that both 5-HT1A and 5-HT2A receptors are present in pre-synaptic thalamic reticular nucleus terminals. Serotonergic-mediated inhibition of GABA release could underlie aberrant thalamocortical physiology described after repetitive consumption of cocaine. Our findings suggest that both 5-HT1A, 5-HT2A and A1 receptors are present in pre-synaptic TRN terminals. 5-HT1A and A1 receptors would down-regulate adenylate cyclase, whereas 5-HT1A would also increase the probability of the opening of G-protein-activated inwardly rectifying K+ channels (GIRK). Sustained opening of GIRK channels would hyperpolarize pre-synaptic terminals activating H-currents, resulting in less GABA release. 5-HT2A-would activate PLC and IP3, increasing intracellular [Ca2+] and thus facilitating GABA release.